Collega Coffee dan Konstruksi Identitas Sosial Konsumen Perempuan - Zalfa Fadhilah Rizqiadni; Hadiati Hadiati; Mohammad Firmansyah (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to examine how female consumers, particularly young mothers, construct and express their social identity through their consumption experiences at Collega Coffee, a coffee shop located in Garut Regency. Using a qualitative approach with a phenomenological method, this research collected data through in-depth interviews with loyal female consumers, supported by social media observations. The use of Social Identity Theory and Symbolic Interactionism reveals that consumers actively form a sense of belonging and self-representation through interactions with the brand and its environment. The study finds that Collega Coffee functions not only as a place to enjoy coffee but also as a symbolic social space where identity construction occurs. Consumers engage in symbolic actions, such as dressing appropriately, selecting conversation topics, and sharing visits on social media, reflecting their alignment with certain social values and groups. The research highlights the role of coffee shops in modern consumer culture, especially as a medium for women to express autonomy, connection, and self-actualization. Ultimately, Collega Coffee is a significant site for the social identity construction of its female customers.